The protective effects of modified palygorskite on the broilers fed a purified zearalenone-contaminated diet. (6th March 2019) - Chen, Yueping; Cheng, Yefei; Wen, Chao; Wang, Wenbo; Kang, Yuru; Wang, Aiqin; Zhou, Yanmin
ABSTRACT: This study was conducted to evaluate the protective effects of dietary modified palygorskite (Pal ) supplementation on broiler chickens fed a purified zearalenone (ZEN )-contaminated diet. A total of 144 1-day-old male chicks were allocated to one of the 3 treatments, with each treatment being composed of 6 replicates of 8 birds each. The birds were fed with a control diet (Control group), the ZEN-contaminated diet (2.0 mg ZEN/kg diet), and the ZEN-contaminated diet supplemented with 1.0 g/kg diet of modified Pal for 42 d, respectively. Compared with control group, feeding ZEN-contaminated diet reduced weight gain and feed conversion efficiency of broilers during the finisher and overall experimental period ( P < 0.05), while the values of these parameters in broilers fed the diet contaminated with ZEN increased after modified Pal administration ( P < 0.05). ZEN challenge increased the 21-d serum aspartate aminotransferase and 42-d serum alanine aminotransferase activities, 42-d relative liver weight, and ZEN residues in the liver at both 21 and 42 d and kidney at 42 d ( P < 0.05). In contrast, birds fed the ZEN-contaminated diet that was supplemented with modified Pal exhibited lower serum alanine aminotransferase activity at 42 d, relative liver weight at 42 d, and hepatic and renal ZEN accumulation at both 21 and 42 d ( P < 0.05), when compared with their counterparts fed the contaminated diet. ZEN contamination decreased superoxide dismutase activity in the serum at 21 d, kidney at 42 d, and liver at both 21 and 42 d, respectively ( P < 0.05). The hepatic and renal malondialdehyde accumulation at 42 d increased, while renal glutathione level at 42 d decreased, when feeding broilers with the ZEN-contaminated diet ( P < 0.05). Dietary modified Pal supplementation reduced hepatic malondialdehyde accumulation, whereas increased renal superoxide dismutase activity in broilers fed a ZEN-contaminated diet at 42 d ( P < 0.05). This finding suggested that dietary modified Pal administration could promote growth performance, reduce hepatonephric ZEN residues, and improve liver function and antioxidant status of broiler chickens receiving a ZEN-contaminated diet.